The theater of death: Andreas Vesalius and his dissections that led to the beginning of anatomy - Mendoza, Vanesa L.; Bohórquez, César A.; Alcívar, Axel; Vásquez, Rafael B.; Bello, Steven R.; Moreno, Christian M. (Revista Gregoriana de Ciencias de la Salud, 2025)
This essay aimed to analyze Andreas Vesalius’s contribution to the development of modern anatomy, highlighting how his human dissection practices and the publication of De Humani Corporis Fabrica in 1543 revolutionized anatomical knowledge. Vesalius’s work marked a turning point by challenging medieval dogmas based on Galen’s teachings, which relied more on animal dissections than on human bodies. The essay explores how Vesalius’s public dissections, performed in anatomical theaters, not only defied academic traditions but also redefined medical education and promoted an empirical approach. These sessions, where the "theater of death" became a space for learning, emphasized the direct observation of the human body as the foundation for understanding its structure and function. Furthermore, it examines the cultural and scientific impact of his work, demonstrating how Vesalius laid the groundwork for a scientific and modern anatomy that remains relevant in contemporary medicine, transcending centuries and traditions to establish himself as the father of modern anatomy.